Injury surveillance of U14 alpine racers in a southern Alberta ski club: Feasibility study with preliminary injury incidence - Christie, M.; Doyle-Baker, P.; Clark, M. (Science and Skiing VII, 2018)
Given the many limiting factors, further investigation is necessary despite the approximated, preliminary injury incidence in the population of U14 ski racers made available by this study. The injury reporting data in this study does suggest commonalities between the injury frequencies and patterns of U14 ski racers and older athletes in the sport. This provides a reason for further research on the topic and critical consideration of when injury prevention programs should be implemented in the sport of alpine ski racing.